Attualità sulle fratture periprotesiche di ginocchio - Melani, T.; Sani, G.; Carulli, C.; Innocenti, M. (Lo Scalpello - Journal, 2018)
PERIPROSTHETIC FRACTURES OF THE KNEE: AN UPDATEPeriprosthetic fractures around the knee after arthroplasty represent a dramatic cause of revision, and their incidenceis likely to rise in the next years as the number of Total Knee Arthroplasties will continue to increase. Our briefoverview supports the fact that functional outcomes after periprosthetic fractures significantly decrease compared tothe preinjury status, with a significant reduction in the mobility of patients. The treatment of periprosthetic kneefractures is extremely challenging and goes from a conservative treatment to open reduction and fixation and, finally,to implant of a megaprosthesis. Decision-making regarding the most appropriate treatment should be made on anindividual basis depending on the location of fractures, stability of the components, and the age and functionalrequests of patients.